Regulatory Breakdown : The Crisis of Confidence in U.S. Regulation - Coglianese, Cary (Book collections on Project MUSE., 2012)
With chapters written by some of the nation's foremost economists, political scientists, and legal scholars, Regulatory Breakdown brings clarity to the heated debate over regulation by dissecting the disparate causes of the current crisis as well as analyzing the most promising solutions to what ails the U.S. regulatory system.